Enhancing OSS E-Government Testing via CEG Method - Gilang, Raka; Sanmorino, A (Jurnal Sistem Informasi dan Teknik Informatika (JAFOTIK), 2025)
The rapid growth of e-government systems has created new opportunities to improve public service delivery, transparency, and efficiency. One prominent initiative in this area is Indonesia’s Online Single Submission (OSS) system, which centralizes licensing and regulatory processes into a digital platform. However, as usage expands, the OSS system faces recurring issues such as functional errors, incomplete test coverage, and inconsistent results that affect user trust and service reliability. To address these challenges, this study applies the Cause-Effect Graphing (CEG) method as a structured testing approach. By translating functional requirements into graphical models, the method enables systematic test case generation that covers both common and complex scenarios. The results show that CEG-based testing achieved higher test coverage (~90%), improved error detection, and reduced redundancy compared to traditional methods. These outcomes demonstrate the potential of CEG to enhance OSS quality and reliability while strengthening confidence in e-government services.